2018
DOI: 10.1155/2018/1075156
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin 1 Mediates Keratinocyte Growth Factor Signaling in Adipose-Derived Stem Cells: Potential Involvement in Adipogenesis

Abstract: Adipogenesis is regulated by a complex network of molecules, including fibroblast growth factors. Keratinocyte growth factor (KGF) has been previously reported to promote proliferation on rat preadipocytes, although the expression of its specific receptor, FGFR2-IIIb/KGFR, is not actually detected in mesenchymal cells. Here, we demonstrate that human adipose-derived stem cells (ASCs) show increased expression of KGF during adipogenic differentiation, especially in the early steps. Moreover, KGF is able to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…In mice, we showed that Sema3s acting via Nrp2 direct the development of Pomc projections from the arcuate to the paraventricular nucleus of the hypothalamus. A role for Nrp1-mediated signaling in pre-adipocyte differentiation has been demonstrated ( Ceccarelli et al., 2018 ). In zebrafish, plxnd1 has been shown to regulate adipose tissue growth by affecting the formation of the extracellular matrix ( Minchin et al., 2015 ), indicating that Semaphorin 3 signaling may affect non-neural mechanisms that contribute to adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, we showed that Sema3s acting via Nrp2 direct the development of Pomc projections from the arcuate to the paraventricular nucleus of the hypothalamus. A role for Nrp1-mediated signaling in pre-adipocyte differentiation has been demonstrated ( Ceccarelli et al., 2018 ). In zebrafish, plxnd1 has been shown to regulate adipose tissue growth by affecting the formation of the extracellular matrix ( Minchin et al., 2015 ), indicating that Semaphorin 3 signaling may affect non-neural mechanisms that contribute to adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…As for the external stimuli, it has been demonstrated that the presence of growth factors in the culture medium could enhance ASCs differentiation (Ceccarelli et al, 2018). Likewise, preconditioning of ASCs with cytokines or other bioactive molecules represents one of the main approaches to boost ASCs immune regulatory functions before their therapeutic administration.…”
Section: Approaches For Optimization Of Ascs Immunomodulatory Efficacymentioning
confidence: 99%
“…Grun and colleagues showed that VEGF-A/NRP1 signalling enhances epidermal cancer stem cell spheroid formation, angiogenic potential, invasion, and migration by activating MAPK signalling [29] . In addition, Ceccarelli et al reported that NRP1 is responsible for keratinocyte growth factordependent ERK and p38 MAPK pathway activation in human adipogenesis [30] . Therefore, we hypothesized that NRP1 may have a significant impact on MAPK pathway activation in BC cells.…”
Section: Discussionmentioning
confidence: 99%